Method for preparing foamable preformed blank by using secondary aluminum and aluminum ash as raw materials
By sorting and alloying the recycled aluminum, and using high-temperature treatment and vacuum desalination technology to treat aluminum ash, composite oxides are generated as foam stabilizers, the problems of low added value of recycled aluminum products and difficulty in treating aluminum ash solid waste are solved, and efficient resource utilization and environmental protection effects are achieved.
Patent Information
- Application Number
- CN202510258527.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-06
AI Technical Summary
Recycled aluminum purification and high-performance aluminum alloy preparation are difficult, and there are environmental and economic problems in the treatment of aluminum ash solid waste.
Regenerated aluminum raw materials are processed through sorting, magnetic separation, flotation and other steps, and alloy elements such as Si, Cu, Fe, Mn, Mg, Zn are added during the smelting and refining process. Then, the aluminum ash is subjected to high-temperature treatment, ball milling, vacuum desalination and high-temperature self-heating sintering to form composite oxides as foam stabilizers and added to the aluminum liquid for foaming treatment.
It has achieved high added value of recycled aluminum products and the effective utilization of aluminum ash solid waste, reduced raw material costs, improved economic value, and realized environmentally friendly closed-loop utilization of resources.
Smart Images

Figure CN119753412A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the application field of recycled aluminum alloys, and specifically relates to a method for preparing a foamable preform by using recycled aluminum and aluminum ash generated in the smelting process as raw materials. Background Art
[0002] Recycled aluminum has the characteristics of low price and low emission, and is developing rapidly. China's recycled aluminum industry is about to face new opportunities. In recent years, with the proposal of green development, the production capacity of my country's electrolytic aluminum industry has reached its upper limit. The reprocessing and use of scrap aluminum alloys has become very important. According to relevant data, the energy consumption of producing 1 ton of recycled aluminum is only 5% of that of original aluminum, and the energy saving and emission reduction effect is obvious. However, because the raw materials of recycled aluminum are widely available and the composition is not fixed, they often contain dozens of elements such as Al, Cu, Fe, Mg, Mn, and Zn, making it difficult to purify, use them for grade retention, or prepare high-performance aluminum alloys. On the other hand, during the remelting and refining process of recycled aluminum, a large amount of aluminum ash solid waste, mainly aluminum nitride, aluminum oxide and aluminum, is generated. Because aluminum nitride decomposes in water and produces harmful gases such as ammonia, the storage and treatment of aluminum ash are extremely difficult. In addition, aluminum ash contains refining agents such as sodium salts and potassium salts, and the composition is complex, making it difficult to recycle and reuse as a resource. How to increase the added value of recycled aluminum products and effectively utilize aluminum ash solid waste is an important issue facing the current development of the recycled aluminum industry.
[0003] Conventional aluminum ash treatment methods are divided into two types: pyrolysis and hydrolysis. The purpose is to remove harmful components in aluminum ash and enrich valuable materials such as alumina. However, due to factors such as high processing costs, complex processes, and low product prices, it is difficult to achieve clear economic value. Using solid phase particles as reinforcements can prepare aluminum-based composite materials, and further used to prepare lightweight aluminum-based foam materials with high added value, which are applied in the fields of automotive lightweight parts and buffering and energy absorption of national defense equipment. Composite solid phase particles (such as SiC particles) with special wettability can provide stability for liquid foam while enhancing the strength of the matrix. The composite material can be quickly cooled after adding a foaming agent to prepare a foamable prefabricated body. However, aluminum ash particles treated by conventional technology have poor wettability with aluminum liquid and are difficult to mix. In addition, the chlorides or fluorides contained in the aluminum ash have a destructive effect on the stability of the foam, making it difficult to use them to prepare high-performance aluminum-based composite materials or aluminum-based foam materials. Summary of the invention
[0004] In view of the above problems, the present invention provides a method for preparing a foamable preform using recycled aluminum and aluminum ash. The present invention aims to solve the problem of resource utilization of recycled aluminum and aluminum ash, and the method can convert these materials into foamable preforms with higher added value. The method of the present invention not only improves the recycling rate of resources, but also provides a new source of raw materials for the production of preforms.
[0005] A method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials comprises the following steps: (1) Sorting and loading of recycled aluminum raw materials The recovered aluminum raw materials are subjected to magnetic separation, flotation and other screening to reduce impurities such as iron, and then placed in a smelting furnace for smelting.
[0006] (2) Alloy smelting The raw materials are melted in a smelting furnace to make the temperature of the aluminum liquid reach 660℃-680℃, the elemental composition in the aluminum liquid is tested, and targeted adjustments are made.
[0007] (3) Slag removal The aluminum ash on the surface produced after smelting is removed, and the aluminum liquid is transferred to a refining furnace, and the temperature of the refining furnace is controlled at 700℃-740℃.
[0008] (4) Ingredients and refining According to the target alloy composition, alloy elements including Si, Cu, Fe, Mn, Mg and Zn are added to stir in the furnace, and the composition of each element in the aluminum liquid is detected to make targeted adjustments;
[0009] Add refining agent and refine for 2h-3h to remove the included gas and solid impurities in the aluminum liquid.
[0010] (5) Slag removal The aluminum ash on the surface produced after refining is removed.
[0011] (6) Recovery and treatment of aluminum from aluminum ash The aluminum ash produced in steps (2) to (5) is recovered and placed in a rotary furnace for high-temperature treatment under a nitrogen protective atmosphere to enrich the aluminum contained therein, and the enriched aluminum is returned to the smelting furnace.
[0012] (7) Ball milling The aluminum ash recovered after high temperature treatment is crushed and ball-milled into fine powder with a particle size of 38μm-100μm according to a ball-to-material ratio of 5:6.
[0013] (8) Vacuum high temperature desalination The ball-milled powder is placed in a vacuum furnace and heated to evaporate the sodium and potassium salts in the powder, which are condensed in a cooling tube and then returned to the refining step after recovery.
[0014] (9) High temperature self-heating sintering The desalted fine powder is mixed with calcium oxide and placed in a calcining furnace for calcination to obtain a composite oxide.
[0015] (10) Screening and adding composite oxide particles to the refined aluminum liquid The composite oxide is passed through an 80-mesh sieve and added into the refined aluminum liquid as a foam stabilizer.
[0016] (11) Add pre-treated foaming agent The temperature of the aluminum liquid is controlled at 630℃-640℃, and the pre-treated foaming agent TiH2 is added into the aluminum liquid and stirred evenly.
[0017] (12) Casting foamable preforms The aluminum liquid is taken out after standing in the resistance furnace for 5s-10s, and cast into a mold preheated to 350°C, and cooled to obtain a preform.
[0018] The above method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials, wherein: In step (4), the target alloy composition content is: Si 9.5%-13.0%, Fe<1.0%, Cu 1.0%-4.0%, Mg<1.0%, Mn<1.0%, Zn<3.0%, Ni<0.5%, and the balance is aluminum and unavoidable impurities. The preferred target alloy is ADC12 aluminum alloy.
[0019] In the step (4), the refining agents used include chlorides and fluorides of sodium and potassium, and the amount used is generally 0.2%-0.4% of the mass of the aluminum alloy melt.
[0020] In the step (6), a high temperature treatment is performed under a nitrogen protective atmosphere, the temperature is controlled at 620°C-780°C, and the high temperature treatment time is 10 minutes. The nitrogen treatment converts the aluminum ash into a phase structure dominated by AlN.
[0021] In step (8), the vacuum high-temperature desalination method is: the ball-milled powder is placed in a vacuum furnace and heated to 780°C-900°C, and the air is evacuated to below 1000Pa and maintained for 30min-60min to evaporate the sodium and potassium salts in the powder.
[0022] In the step (9), the desalted fine powder and calcium oxide are mixed and placed in a calcining furnace for calcination, the amount of calcium oxide added is 2%-4% of the mass of the fine powder, the sintering temperature is 1200°C-1400°C, the calcination time is 20min-40min, and the obtained composite oxide has aluminum oxide, silicon dioxide, iron oxide, magnesium oxide, and sodium oxide as main components. The nitrogen generated during calcination is recovered and used for the treatment of aluminum ash.
[0023] In the step (10), the foam stabilizer is added to the refined aluminum liquid by stirring at a temperature of 640°C-660°C and a stirring rate of 600rpm-1000rpm. The amount of the foam stabilizer added is 6%-12% of the mass of the aluminum liquid, and the stirring time is 120s-300s.
[0024] In the step (11), the amount of TiH2 added is 1.1%-1.2% of the mass of the aluminum liquid, the stirring time is 60s-180s, and the stirring rate is 600rpm-1000rpm.
[0025] In the step (11), the pretreatment refers to heating the TiH2 powder in a resistance furnace, usually raising the temperature to 380°C-420°C, keeping the temperature for 20min-40min, and then cooling down with the furnace.
[0026] In the step (12), the density of the preform obtained is 1.4 g / cm 3 -1.7g / cm 3 .
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. Low raw material cost and high economic value. Recycled aluminum waste is used as raw material and aluminum ash solid waste is made into bubble stabilizer. The raw material source is wide and the cost is low. The prepared foamable preform product has higher economic benefits and better economic value than ordinary aluminum alloy.
[0028] 2. Achieve closed-loop utilization of resources in the whole process of recycled aluminum preform preparation, with high environmental benefits. Aluminum ash, a solid hazardous waste, is recycled, and the unit weight of aluminum ash is greater than or equal to the amount of aluminum ash produced. The refining agent added in the intermediate link can be recycled as a refining agent raw material after vacuum desalination of aluminum ash. There is no wastewater or solid waste discharge in the whole process, which has good environmental benefits.
[0029] 3. The production process is carbon-saving and energy-saving. The temperature of adding aluminum ash into the prefabricated body is low, and it can be mixed without heating after the composition of the aluminum liquid is adjusted. The aluminum ash treatment process utilizes the aluminum heat reaction, and no fuel needs to be added. The overall process is carbon-saving and energy-saving.
[0030] 4. Aluminum ash is used to replace the metal Ca added in the conventional aluminum foam preparation process, further reducing the production cost. The addition of Ca in the aluminum foam foaming process will form a hard and brittle phase CaAl2Si2 in the foam. During compression, stress is concentrated here, resulting in cracks and indirect fractures in the aluminum matrix. The addition of the composite oxide of the present invention can promote grain refinement and improve material properties. The composite oxide of the present invention can replace most of Ca to play a role in viscosity-enhancing and stabilizing pores, effectively reducing the amount of CaAl2Si2 in the foam, and the composite oxide is mainly distributed on the surface of the bubble wall in the aluminum foam ( Figure 8), reducing the brittle fracture of the pores caused by stress concentration, and the addition of composite oxides effectively reduces the size of eutectic silicon grains and improves the grain distribution. In general, the commonly used viscosity enhancer Ca is not added during the preparation of the preform, and the addition of composite oxides enhances the strength of the matrix while avoiding the problem of high material brittleness caused by high Si, Mg, Cu, and Fe contents through grain refinement ( Fig.11 ).
[0031] 5. The aluminum ash treatment process includes a vacuum desalting step to remove fluoride, chloride and other substances that affect foaming and affect the subsequent foaming process. In the traditional process, aluminum ash still contains aluminum nitride and fluoride, chloride and other substances that affect foaming after calcination and water washing ( Figure 7 ).
[0032] 6. Aluminum ash is treated with nitrogen protection to improve the recovery rate of metallic aluminum in aluminum ash, and the aluminum ash is converted into a phase structure dominated by AlN. Then, it is vacuum desalted and high-temperature self-thermal oxidation to produce composite oxides, and CaO is added to react to generate a special high specific surface area morphology. It can significantly improve the wettability between composite oxides and aluminum liquid, and it is easy to react and wet with components such as Mg and Cu in a specific proportion in the alloy composition. It is easy to adsorb gas during stirring, reducing the degassing loss of the foaming agent during stirring. A large number of bubble nuclei are generated in the preform after solidification, which helps to inhibit bubble drainage in the subsequent foaming process. The surface expansion range is small during expansion, and it is easy to obtain better surface quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a flow chart of the preparation process of the present invention; Figure 2 The microscopic structure of aluminum ash under electron microscope in the present invention that has not been desalted under vacuum and high temperature; Figure 3 The microscopic structure of aluminum ash after vacuum high-temperature desalination in the present invention under an electron microscope; Figure 4 This is the energy spectrum of aluminum ash after vacuum high-temperature desalination in the present invention; Figure 5 XRD analysis of aluminum ash treated with nitrogen but not desalted in the present invention; Figure 6 XRD analysis of aluminum ash after vacuum high temperature desalination treatment in the present invention; Figure 7 This is the XRD analysis of aluminum ash after water washing in the traditional process; Figure 8 The microstructure of the composite oxide on the surface of the bubble wall under an electron microscope in the present invention; Fig. 9The microstructure of the regenerated aluminum after the composite oxide is added under an electron microscope in the present invention; Fig.10 is a cross-sectional view of the preform in the present invention; Fig.11 It is a compression comparison curve of the foamed aluminum formed after the preform is foamed in the present invention; Fig.12 It is the expansion rate curve during the foaming process of the preform in the present invention. DETAILED DESCRIPTION
[0034] The following specific embodiments illustrate the implementation of the present invention. People familiar with the technology can easily understand the advantages and effects of the present invention from the contents disclosed in the present specification. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0035] Example 1 A method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials, the process flow is as follows Figure 1 The specific steps are as follows: (1) Sorting and loading of recycled aluminum raw materials The recovered aluminum raw materials are subjected to magnetic separation, flotation and other screening to reduce impurities such as iron, and then placed in a smelting furnace for smelting.
[0036] (2) Alloy smelting The raw materials are melted in a smelting furnace to make the temperature of the aluminum liquid reach 660℃-680℃, the elemental composition in the aluminum liquid is tested, and targeted adjustments are made.
[0037] As shown in Table 1, the main component contents of the melted raw materials are: Si 6.66%-7.15%, Cu 1.28%-1.37%, Mg0.307%-0.325%, Mn 0.193%-0.199%, Fe 0.862%-0.890%, Zn 0.854%-0.878%, Ni 0.0502%-0.0547%, Al 89.13%-89.84%. The average contents of the main components in the melted raw materials are: Si 6.94%, Cu 1.32%, Mg0.315%, Mn 0.196%, Fe 0.875%, Zn 0.867%, Ni 0.0520%, Al 89.43%.
[0038] Table 1 Composition of aluminum alloy after smelting in the present invention
[0039] (3) Slag removal The aluminum ash on the surface produced after smelting is removed, and the aluminum liquid is transferred to a refining furnace, and the temperature of the refining furnace is controlled at 700℃-740℃.
[0040] (4) Ingredients and refining According to the target alloy composition, alloy elements such as Si, Cu, Fe, Mn, Mg, and Zn are added for stirring in the furnace, the elemental composition in the aluminum liquid is detected, and targeted adjustments are made.
[0041] The target alloy is ADC12 aluminum alloy, and the chemical composition content is: Si 9.6%-12%, Fe<0.9%, Cu 1.5%-3.5%, Mg<0.3%, Mn<0.5%, Zn<1.0%, Ni<0.5%, and the balance is aluminum and unavoidable impurities.
[0042] Refining agent NaCl was added in an amount of 0.2% of the mass of the aluminum alloy melt, and the refining was carried out for 2 hours to remove the included gas and solid impurities in the aluminum liquid. The average content of components in the aluminum liquid after refining was: Si 10.77%, Cu 1.54%, Mn 0.262%, Fe0.859%, Mg 0.245%, Zn 0.755%, Ni 0.0465%, Al 85.52%, and unavoidable impurities. The test results and average values of the four groups are shown in Table 2.
[0043] Table 2 Test results and average values of four groups of experiments
[0044] (5) Slag removal The aluminum ash on the surface produced after refining is removed.
[0045] (6) Recovery and treatment of aluminum from aluminum ash The aluminum ash produced in steps (2) to (5) is recovered and placed in a rotary furnace for high-temperature treatment under a nitrogen protective atmosphere at a temperature of 620°C-650°C for 10 minutes to enrich the aluminum contained therein. The enriched aluminum is then returned to the smelting furnace. Figure 5 The nitrogen treatment transforms the aluminum ash into a phase structure dominated by AlN.
[0046] (7) Ball milling The aluminum ash recovered after high temperature treatment is crushed and ball-milled into fine powder with a particle size of 38μm-100μm according to a ball-to-material ratio of 5:6.
[0047] (8) Vacuum high temperature desalination The ball-milled powder is placed in a vacuum furnace and heated to 780°C-900°C, and the air is evacuated to below 1000Pa for 30 minutes to evaporate the sodium salt, potassium salt, etc. in the powder and condense in the cooling tube. After recovery, it returns to the refining step. Figure 6 This is the XRD analysis of aluminum ash after vacuum and high temperature desalination treatment.
[0048] (9) High temperature self-heating sintering The desalted fine powder and calcium oxide are mixed and placed in a calcining furnace. The amount of calcium oxide added is 2% of the mass of the fine powder. The powder is ignited to raise the sintering temperature to 1200°C. The mixture is calcined for 30 minutes to obtain a composite oxide with aluminum oxide, silicon dioxide, iron oxide, magnesium oxide and sodium oxide as the main components. The nitrogen generated by calcination is recovered for the treatment of aluminum ash.
[0049] The microstructure of aluminum ash without vacuum calcination treatment under electron microscope is as follows: Figure 2 The microstructure and energy spectrum of aluminum ash after vacuum calcination are shown in Figure 3 , Figure 4 shown. Figure 2 The particles of medium-aluminum ash are irregular in shape, have a rough surface, and may contain a variety of different crystal structures or phases. Figure 3 After calcination, the morphology of aluminum ash particles is more regular, forming a specific crystal structure, the particle surface is smoother, and the agglomeration between particles is reduced.
[0050] (10) Screening and adding composite oxide particles to the refined aluminum liquid The composite oxide was passed through an 80-mesh sieve and then added as a foam stabilizer into the refined aluminum liquid at a temperature of 640°C-660°C and a stirring rate of 1000 rpm. The amount of foam stabilizer added was 6% of the mass of the aluminum liquid and the stirring time was 120 s.
[0051] Figure 8 The microstructure under electron microscope is that the composite oxide is added into the aluminum liquid and distributed on the bubble wall surface; Fig. 9 This is the microstructure of aluminum liquid under electron microscope after adding composite oxide.
[0052] (11) Add pre-treated foaming agent The aluminum liquid temperature was controlled at 637°C, and the pre-treated foaming agent TiH2 was added to the aluminum liquid and stirred evenly. The amount of TiH2 added was 1.15% of the aluminum liquid mass, the stirring time was 60s, and the stirring rate was 600rpm.
[0053] (12) Casting into foamable preform The aluminum liquid was placed in the resistance furnace for 5s-10s and then taken out and cast into a mold preheated to 350°C. The preform was cooled to obtain a preform with a density of 1.44g / cm3 .
[0054] The cross section of the prepared preform is as follows Fig.10 As shown in the figure, the compression comparison curve of the foamed aluminum formed after the preform is foamed is as follows Fig.11 As shown, the expansion rate curve is Fig.12 As shown. Fig.11 It can be seen that the fluctuation of the compression curve of the aluminum-based foam material prepared by adding 6% composite oxide as a foam stabilizer is significantly smaller than that of the aluminum-based foam material prepared by adding 3% metal Ca as a viscosity enhancer, which significantly improves the overall mechanical properties and energy absorption. Fig.12 It can be seen that after about 15 minutes, the expansion rate of the preform during foaming begins to increase significantly, indicating that the material begins to experience rapid thermal expansion. The shape of the entire curve shows that the expansion rate is a function of time, and within a specific time range, the expansion rate will increase significantly.
[0055] Example 2 A method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials, the process flow is as follows Figure 1 The specific steps are as follows: (1) Sorting and loading of recycled aluminum raw materials The recovered aluminum raw materials are subjected to magnetic separation, flotation and other screening to reduce impurities such as iron, and then placed in a smelting furnace for smelting.
[0056] (2) Alloy smelting The raw materials are melted in a smelting furnace to make the temperature of the aluminum liquid reach 660℃-680℃, the elemental composition in the aluminum liquid is tested, and targeted adjustments are made.
[0057] As shown in Table 1, the main component contents of the melted raw materials are: Si 6.66%-7.15%, Cu 1.28%-1.37%, Mg0.307%-0.325%, Mn 0.193%-0.199%, Fe 0.862%-0.890%, Zn 0.854%-0.878%, Ni 0.0502%-0.0547%, Al 89.13%-89.84%. The average contents of the main components in the melted raw materials are: Si 6.94%, Cu 1.32%, Mg0.315%, Mn 0.196%, Fe 0.875%, Zn 0.867%, Ni 0.0520%, Al 89.43%.
[0058] (3) Slag removal The aluminum ash on the surface produced after smelting is removed, and the aluminum liquid is transferred to a refining furnace, and the temperature of the refining furnace is controlled at 700℃-740℃.
[0059] (4) Ingredients and refining According to the target alloy composition, alloy elements such as Si, Cu, Fe, Mn, Mg, and Zn are added for stirring in the furnace, the composition of each element in the aluminum liquid is detected, and targeted adjustments are made.
[0060] The target alloy is ZL108 aluminum alloy, and its composition content is: Si 11.0%-13.0%, Fe<1.0%, Cu 1.0%-2.0%, Mg 0.4%-1.0%, Mn<0.9%, Zn<1.0%, Ni<0.05%, and the balance is aluminum and unavoidable impurities.
[0061] Add refining agent NaCl, 0.3% of the mass of aluminum alloy melt, and refine for 3 hours to remove the included gas and solid impurities in the aluminum liquid. The average content of components in the aluminum liquid after refining is: Si 12%, Cu 1.5%, Mn 0.223%, Fe 0.746%, Mg 0.470%, Zn 0.973%, and the rest is aluminum and unavoidable impurities.
[0062] (5) Slag removal The aluminum ash on the surface produced after refining is removed.
[0063] (6) Recovery and treatment of aluminum from aluminum ash The aluminum ash produced in steps (2) to (5) is recovered and placed in a rotary furnace for high-temperature treatment under a nitrogen protective atmosphere. The temperature is controlled at 650°C-700°C for 10 minutes to enrich the aluminum contained therein. The enriched aluminum is returned to the smelting furnace.
[0064] (7) Ball milling The aluminum ash recovered after high temperature treatment is crushed and ball-milled into fine powder with a particle size of 38μm-100μm according to a ball-to-material ratio of 5:6.
[0065] (8) Vacuum high temperature desalination The ball-milled powder is placed in a vacuum furnace and heated to 780°C-900°C, and the air is evacuated to below 1000Pa for 40 minutes to evaporate the sodium salt and potassium salt in the powder, condense in the cooling tube, and then returned to the refining step after recovery.
[0066] (9) High temperature self-heating sintering The desalted fine powder and calcium oxide are mixed and put into a calcining furnace. The amount of calcium oxide added is 3% of the mass of the fine powder. The powder is ignited to increase the sintering temperature to 1300°C. The mixture is calcined for 20 minutes to obtain a composite oxide with aluminum oxide, silicon dioxide, iron oxide, magnesium oxide and sodium oxide as the main components. The nitrogen generated by the calcination is recovered for the treatment of aluminum ash.
[0067] (10) Screening and adding composite oxide particles to the refined aluminum liquid The composite oxide was passed through an 80-mesh sieve and then added as a foam stabilizer into the refined aluminum liquid at a temperature of 640°C-660°C and a stirring rate of 800 rpm. The amount of foam stabilizer added was 12% of the mass of the aluminum liquid and the stirring time was 180 s.
[0068] (11) Add pre-treated foaming agent The temperature of the aluminum liquid was controlled at 630°C, and the pretreated foaming agent TiH2 was added into the aluminum liquid and stirred evenly. The amount of TiH2 added was 1.2% of the mass of the aluminum liquid. The stirring time was 180s and the stirring rate was 800rpm.
[0069] (12) Casting into foamable preform The aluminum liquid was placed in the resistance furnace for 5s-10s and then taken out and cast into a mold preheated to 350°C. The preform was cooled to obtain a preform with a density of 1.69g / cm 3 .
[0070] Example 3 A method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials, the process flow is as follows Figure 1 The specific steps are as follows: (1) Sorting and loading of recycled aluminum raw materials The recovered aluminum raw materials are subjected to magnetic separation, flotation and other screening to reduce impurities such as iron, and then placed in a smelting furnace for smelting.
[0071] (2) Alloy smelting The raw materials are melted in a smelting furnace to make the temperature of the aluminum liquid reach 660℃-680℃, the elemental composition in the aluminum liquid is tested, and targeted adjustments are made.
[0072] As shown in Table 1, the main component contents of the melted raw materials are: Si 6.66%-7.15%, Cu 1.28%-1.37%, Mg0.307%-0.325%, Mn 0.193%-0.199%, Fe 0.862%-0.890%, Zn 0.854%-0.878%, Ni 0.0502%-0.0547%, Al 89.13%-89.84%. The average contents of the main components in the melted raw materials are: Si 6.94%, Cu 1.32%, Mg0.315%, Mn 0.196%, Fe 0.875%, Zn 0.867%, Ni 0.0520%, Al 89.43%.
[0073] (3) Slag removal The aluminum ash on the surface produced after smelting is removed, and the aluminum liquid is transferred to a refining furnace, and the temperature of the refining furnace is controlled at 700℃-740℃.
[0074] (4) Ingredients and refining According to the target alloy composition, alloy elements such as Si, Cu, Fe, Mn, Mg, and Zn are added for stirring in the furnace, the elemental composition in the aluminum liquid is detected, and targeted adjustments are made.
[0075] The target alloy is YL113 aluminum alloy, and its composition content is: Si 9.5%-11.5%, Fe<1.0%, Cu 2.0%-3.0%, Mg≤0.1%, Mn<0.5%, Zn<2.9%, Ni<0.3%, and the balance is aluminum and unavoidable impurities.
[0076] The refining agent is a mixture of NaCl and KCl in a mass ratio of 1:1, and the amount added is 0.4% of the mass of the aluminum alloy melt. Refining is carried out for 2.5 hours to remove the included gas and solid impurities in the aluminum liquid. The average content of the components in the aluminum liquid after refining is: Si 11%, Mg 0.1%, Cu 2.3%, Fe 0.52%, Mn 0.34%, Zn 0.08%, and the balance is aluminum and unavoidable impurities.
[0077] (5) Slag removal The aluminum ash on the surface produced after refining is removed.
[0078] (6) Recovery and treatment of aluminum from aluminum ash The aluminum ash produced in steps (2) to (5) is recovered and placed in a rotary furnace for high-temperature treatment under a nitrogen protective atmosphere at a temperature of 700°C to 780°C for 10 minutes to enrich the aluminum contained therein. The enriched aluminum is then returned to the smelting furnace.
[0079] (7) Ball milling The aluminum ash recovered after high temperature treatment is crushed and ball-milled into fine powder with a particle size of 38μm-100μm according to a ball-to-material ratio of 5:6.
[0080] (8) Vacuum high temperature desalination The ball-milled powder is placed in a vacuum furnace and heated to 780°C-850°C, and the air is evacuated to below 1000Pa for 60 minutes to evaporate the sodium salt and potassium salt in the powder, and condense in the cooling tube, and then returned to the refining step after recovery.
[0081] (9) High temperature self-heating sintering The desalted fine powder and calcium oxide are mixed and put into a calcining furnace. The amount of calcium oxide added is 4% of the mass of the fine powder. The powder is ignited to increase the sintering temperature to 1400°C. The mixture is calcined for 20 minutes to obtain a composite oxide with aluminum oxide, silicon dioxide, iron oxide, magnesium oxide and sodium oxide as the main components. The nitrogen generated by the calcination is recovered for the treatment of aluminum ash.
[0082] (10) Screening and adding composite oxide particles to the refined aluminum liquid The composite oxide was passed through an 80-mesh sieve and then added as a foam stabilizer into the refined aluminum liquid at a temperature of 640°C-660°C and a stirring rate of 600 rpm. The amount of foam stabilizer added was 10% of the mass of the aluminum liquid, and the stirring time was 300 s.
[0083] (11) Add pre-treated foaming agent The temperature of the aluminum liquid is controlled at 640°C, and the pretreated foaming agent TiH2 is added to the aluminum liquid and stirred evenly. The amount of TiH2 added is 1.2% of the mass of the aluminum liquid. The stirring time is 120s and the stirring rate is 1000rpm.
[0084] (12) Casting into foamable preform The aluminum liquid was placed in the resistance furnace for 5s-10s and then taken out and cast into a mold preheated to 350°C. The preform was cooled to obtain a preform with a density of 1.58g / cm 3 .
Claims
1. A method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials, characterized in that: The steps include: (1) Sorting and loading of recycled aluminum raw materials: The recycled aluminum raw materials are subjected to magnetic separation and flotation screening to reduce impurities therein, and then placed in a smelting furnace for smelting; (2) Alloy smelting: Melt the raw materials in a smelting furnace to make the aluminum liquid temperature reach 660℃-680℃, and detect the elemental composition in the aluminum liquid; (3) Slag removal: Remove the aluminum ash on the surface after smelting, and transfer the aluminum liquid to the refining furnace. The temperature of the refining furnace is controlled at 700℃-740℃; (4) Ingredients and refining: According to the target alloy composition, alloy elements including Si, Cu, Fe, Mn, Mg and Zn are added to stir in the furnace, and the composition of each element in the aluminum liquid is detected; Add refining agent and refine for 2h-3h to remove the included gas and solid impurities in the aluminum liquid; (5) Slag removal: Remove the aluminum ash on the surface produced after refining; (6) Recovery and treatment of aluminum in aluminum ash: The aluminum ash produced in steps (2) to (5) is recovered and placed in a rotary furnace for high-temperature treatment under a nitrogen protective atmosphere at a temperature of 620°C-780°C for 10 minutes. The nitrogen treatment converts the aluminum ash into a phase structure dominated by AlN and enriches the aluminum contained therein. The enriched aluminum is returned to the smelting furnace; (7) Ball milling: The aluminum ash recovered after high temperature treatment is crushed and ball-milled into fine powder with a particle size of 38μm-100μm according to a ball-to-material ratio of 5:6; (8) Vacuum high temperature desalination: The ball-milled powder is placed in a vacuum furnace for heating to evaporate the sodium and potassium salts in the powder and condense in a cooling tube, and then returned to the refining step after recovery; (9) High temperature self-heating sintering: The desalted fine powder and calcium oxide are mixed and placed in a calcining furnace for calcination, wherein the amount of calcium oxide added is 2%-4% of the mass of the fine powder to obtain a composite oxide; (10) Screening and adding composite oxide particles to the refined aluminum liquid: The composite oxide is passed through an 80-mesh sieve and added to the refined aluminum liquid as a foam stabilizer; (11) Add pretreated foaming agent: The temperature of the aluminum liquid is controlled at 630℃-640℃, and the pre-treated foaming agent TiH2 is added to the aluminum liquid, and stirred evenly; (12) Casting foamable preforms: The aluminum liquid was placed in the resistance furnace for 5s-10s and then taken out and cast into a mold preheated to 350°C. The preform was cooled to obtain a preform with a density of 1.4g / cm 3 -1.7g / cm 3 .
2. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In the step (4), the target alloy composition content is: Si 9.5%-13.0%, Fe<1.0%, Cu 1.0%-4.0%, Mg<1.0%, Mn<1.0%, Zn<3.0%, Ni<0.5%, and the balance is aluminum and unavoidable impurities.
3. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In the step (4), the refining agent used includes chlorides and fluorides of sodium and potassium, and the amount used is 0.2%-0.4% of the mass of the aluminum alloy melt.
4. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In step (8), the vacuum high-temperature desalination method is: the ball-milled powder is placed in a vacuum furnace and heated to 780°C-900°C, and the air is evacuated to below 1000Pa and maintained for 30min-60min to evaporate the sodium and potassium salts in the powder.
5. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In the step (9), the sintering temperature is 1200° C.-1400° C., the calcination time is 20 min-40 min, and the obtained composite oxide has aluminum oxide, silicon dioxide, iron oxide, magnesium oxide and sodium oxide as main components.
6. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In the step (10), the foam stabilizer is added to the refined aluminum liquid by stirring at a temperature of 640° C.-660° C. and a stirring rate of 600 rpm-1000 rpm.
7. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In the step (10), the amount of foam stabilizer added is 6%-12% of the mass of the aluminum liquid, and the stirring time is 120s-300s.
8. The method for preparing a foamable preform using recycled aluminum and aluminum ash as raw materials according to claim 1, characterized in that: In the step (11), the amount of TiH2 added is 1.1%-1.2% of the mass of the aluminum liquid, the stirring time is 60s-180s, and the stirring rate is 600rpm-1000rpm; the pretreatment refers to heating the TiH2 powder in a resistance furnace, raising the temperature to 380℃-420℃, keeping the temperature for 20min-40min, and then cooling down with the furnace.
Citation Information
Patent Citations
Casting process for production of automobile steering device shell
CN105312532A
Preparation method of closed-cell foam aluminum alloy
CN108149050A
Preparation method of foamed aluminum material with uniform foam holes
CN108842080A
Method for preparing foam microcrystalline glass from secondary aluminum ash
CN115028367A
Method for preparing foamed aluminum net forming part based on liquid phase method foaming
CN116516204A
Cited By
Method for preparing high-performance refractory material raw material through synchronous nitrogen fixation and detoxification of secondary aluminum ash under high-temperature nitrogen atmosphere
CN121202540A